Influencing Factors in the Performance of Higher Education in Colombia, Year 2019 (Global Journal of Human-Social Science, 2021)
The purpose of this article is to explain the factors that influence academic performance in higher education in Colombia for the year 2019. Therefore, an ordinal response econometric model was estimated: ordered logit based on the results of the ICFES-SABER PRO higher education state exam applied in 2019. The dependent variable in this case is polytomous, covering the categorization insufficient, minimum, satisfactory and excellent, which corresponds to the results obtained in the test from lowest to highest; and as explanatory variables we considered gender, origin of the student, study modality, nature of the university, scholarship, parents' education, socioeconomic stratum, access to technological tools, and weekly hours worked by the students. The results obtained show that being male, being born in the city, studying in person, studying in a public university, having a scholarship, having parents with a higher level of education, belonging to a high economic stratum, access to technological tools such as computer and internet increase the probability of obtaining a better academic performance.
Keywords: academic performance; higher education in colombia; saber pro ICFES tests; ordered logit model